2017
DOI: 10.1016/j.nlm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile treatment with a novel mGluR2 agonist/mGluR3 antagonist compound, LY395756, reverses learning deficits and cognitive flexibility impairments in adults in a neurodevelopmental model of schizophrenia

Abstract: Schizophrenia (SCZ) is a neurodevelopmental psychiatric disorder, in which cognitive function becomes disrupted at early stages of the disease. Although the mechanisms underlying cognitive impairments remain unclear, N-methyl-D-aspartate receptors (NMDAR) hypofunctioning in the prefrontal cortex (PFC) has been implicated. Moreover, cognitive symptoms in SCZ are usually unresponsive to treatment with current antipsychotics and by onset, disruption of the dopamine system, not NMDAR hypofunctioning, dominates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…; Li et al . ). NR2B protein levels are substantially reduced, as shown by western blot analysis, but this approach cannot distinguish the regional or laminar specificity of this deficiency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Li et al . ). NR2B protein levels are substantially reduced, as shown by western blot analysis, but this approach cannot distinguish the regional or laminar specificity of this deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…; Li et al . ). Pups were usually born on E21/P0, and were weaned and rehoused on postnatal day 21 (P21).…”
Section: Methodsmentioning
confidence: 97%
“…In our recent study (Li et al, 2017), we found that targeting mGluR2/3 in the early stage can correct NMDAR hypofunction and has a beneficial effect for cognition deficits observed in adult MAM rats. However, the mechanism of how it works was untested.…”
Section: Introductionmentioning
confidence: 89%
“…Specifically, activation of mGluR2/3 negatively modulates synaptic transmission by reducing presynaptic glutamate release (Mateo and Porter, 2007). In contrast, postsynaptic mGluR2/3 enhances neuronal excitability (Jin et al, 2017) and AMPARs and NMDARs function directly (Li et al, 2017; Li et al, 2015a; Li et al, 2015b; Tyszkiewicz et al, 2004; Wang et al, 2013; Xi et al, 2011). Although clinical trials of mGluR2/3 agonists in adult patients with SZ have yielded controversial results (Downing et al, 2014; Patil et al, 2007), emerging data suggest that pharmacological activation of mGluR2/3 modulates glutamate neurotransmission and affects NMDAR function, holding the promise of this treatment strategy for the glutamate hypofunction hypothesis (Li et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study Li et al first described a decrease in NMDA receptor expression in an animal model, and then by treating the animals with LY39, an agonist of mGluR, corrected the disrupted NMDA receptor expression. Furthermore, they observed that learning deficits and cognitive flexibility improved in treated animals, and thus found a correlation between the expression level of BDNF and NMDA and the symptoms of schizophrenia [ 26 ]. In a germ free mice line, decreased expression levels of BDNF and NMDA receptors were found in the cortex and hippocampus [ 27 ].…”
Section: Introductionmentioning
confidence: 99%